2021
DOI: 10.1016/j.injury.2021.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Molecular enhancement of fracture healing - Is there a role for Bone Morphogenetic Protein-2, parathyroid hormone, statins, or sclerostin-antibodies?

Abstract: Enhancement of fracture healing has been a hot topic over the last two decades. This narrative review article is aimed to provide an update on current clinical use and evidence on four clinically available agents in the treatment of fracture healing: bone morphogenetic proteins-2 (BMP-2), parathyroid hormone, statins and sclerostin-antibodies. After first promising results from animal and clinical studies in the early 20 0 0s, BMP-2 was studied mainly in open tibia shaft fractures treated with intramedullary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…However, supraphysiological concentrations are needed for a good outcome, which results in increased side effects like inflammation and tissue swelling. (7)(8)(9) Therefore, there is the urgent need to identify new molecules to improve fracture healing.…”
Section: Introductionmentioning
confidence: 99%
“…However, supraphysiological concentrations are needed for a good outcome, which results in increased side effects like inflammation and tissue swelling. (7)(8)(9) Therefore, there is the urgent need to identify new molecules to improve fracture healing.…”
Section: Introductionmentioning
confidence: 99%
“…Even in long bone non-unions, rhBMP-2 promoted faster bone healing (HR = 2.78; 95% CI 1.4-5.6, p < 0.001) and higher union rates (89% vs. 47%; p < 0.001) compared to no-BMP group [20]. Although previous studies reported no advantages of rhBMP-2 on fracture healing, recent studies have reported better fracture healing than control or even autogenous iliac bone graft [21,22].…”
Section: Discussionmentioning
confidence: 91%
“…This study revealed that the rhBMP-2 could enhance the healing process of the fractured vertebral body. Regarding the mechanism of rhBMP-2 for fracture healing, Liu et al reported that rhBMP-2 accelerated the migration of bone marrow mesenchymal stem cells via the CDC42/PAK1/LIMK1 pathway and enhanced the fracture healing process [21]. Another study demonstrated the BMP-2-dependent fracture healing through tight control of chemokine C-X-C motif-ligand-12 (CXCL12) expression [23].…”
Section: Discussionmentioning
confidence: 99%
“…There are several signaling molecules and growth factors to enhance cell migration and osteogenic differentiation, which can also be incorporated into coatings [ 4 , 7 ]. Hereby, the Bone Morphogenetic Protein (BMP) -2 is the most well-researched, which has also been used for clinical application [8] .…”
Section: Implant Advancementmentioning
confidence: 99%